Subsequent fertility after cesarean scar pregnancy: a retrospective analysis - Xiaoxiao Jin; Manman Liu; Panxi Zhang; Lingzhi Zheng; Feng Qi (BMC, 2023)
Abstract Background Cesarean scar pregnancy (CSP) refers to the implantation and growth of the gestational sac at a uterine scarring site due to a previous cesarean section. The effects of CSP on subsequent fertility have emerged as a clinical issue of importance in gynecology and obstetrics in China owing to the increasing rate of cesarean section over the past 30 years in combination with the abolition of the national family planning policy, allowing for subsequent pregnancies. Therefore, we aimed to investigate the effects of CSP treatment on subsequent fertility and pregnancy outcomes. Methods The study consecutively enrolled 499 women treated for CSP at Taizhou Hospital between January 2009 and December 2018. The study outcomes were the rate of secondary infertility and pregnancy outcomes. Clinical information was collected at the time of admission for CSP treatment. Information on subsequent fertility and pregnancy outcomes was collected via telephonic follow-up. Results Among the 499 women who met the inclusion criteria for CSP, 48 were lost to follow-up. Most women (74.9%, 338/451) did not express the desire for a subsequent pregnancy after CSP treatment. Among the 113 women who initially desired a subsequent pregnancy, 62 finally abandoned fertility plans. Among the 51 women who pursued pregnancy, 48 pregnancies were recorded in 43 women, infertility secondary to CSP treatment was identified in 15.7% (8/51) of women, and 60.8% (31/51) of women achieved full-term pregnancy, with placenta accreta spectrum identified in two women, one requiring a hysterectomy during cesarean section due to massive bleeding. Among the 16 women treated with uterine artery embolization combined with uterine aspiration and 18 women treated by ultrasound-guided local lauromacrogol injection combined with uterine aspiration, a successful full-term pregnancy rate of 68.8% (11/16) and 88.9% (16/18), respectively, was achieved. There were five cases of recurrent CSP among all 76 pregnancies (6.6%). Conclusion Over a long-term follow-up of women after CSP treatment, a high successful fertility rate was identified, with also an increased CSP recurrence rate. Uterine artery embolization combined with uterine aspiration and ultrasound-guided local lauromacrogol injection combined with uterine aspiration showed high rates of successful post-treatment fertility and pregnancy.